A comparison of extra-curricular school sport participation motives between male and female froshies - Sanes, Ludabella Aurora C.; Pagalan, Abelano (2011)
This study aimed to provide the reader with deeper understanding of students' attitudes toward extra curricular school sport and their motives of participating in such activities.
The study found out that both boys and girls cited fun as their number one motive, therefore showing a similarity between both genders. However, the study found that girls' motives were more sociologically based than their male counterparts whose motives were more widespread. Therefore, this study found extra curricular activities to be a starting point for the positive development of children's attitudes towards sport.
In conclusion, this research suggests that fun and enjoyable activities in school encourage pupils to participate in sport out of school, therefore implying that teachers should pay close attention to the fun element of their session in order to aid in the pupils' development of positive attitudes towards sport and to influence lifelong participation.
Keywords: Sports psychology